2022
DOI: 10.1021/acs.jafc.2c02521
|View full text |Cite
|
Sign up to set email alerts
|

Designing Stacked Assembly of Type III Rubisco for CO2 Fixation with Higher Efficiency

Abstract: The slow catalytic rate of the carboxylation enzyme D-ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) is a major barrier to increasing the rate of carbon assimilation from the atmosphere into the biosphere. It is of great importance to establish a method to improve the carboxylation efficiency of Rubisco. Inspired by the assembly of Rubisco in carboxysomes, herein, we presented a rational protein engineering approach for the construction of one-dimensional (1D) protein arrays of type III Rubisco thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Our results demonstrate how a small number of residues-only seven mutations-can enable an increase in oligomeric state, providing insight into the requisite degree of plasticity necessary for innovation of larger oligomeric states. Recent studies have demonstrated how few mutations can be introduced to proteins, resulting in radical increases in oligomerization that are more accurately described as non-native protein fibrils (27)(28)(29). In comparison, our study focuses on understanding the structural basis underlying transitions between oligomeric states found in nature, as our mutational engineering of the 2-to-6 enzyme recapitulates the evolutionary trajectory taken by form II RuBisCOs when assembling hexamers from dimers.…”
Section: Engineering Increased Oligomeric Complexitymentioning
confidence: 99%
“…Our results demonstrate how a small number of residues-only seven mutations-can enable an increase in oligomeric state, providing insight into the requisite degree of plasticity necessary for innovation of larger oligomeric states. Recent studies have demonstrated how few mutations can be introduced to proteins, resulting in radical increases in oligomerization that are more accurately described as non-native protein fibrils (27)(28)(29). In comparison, our study focuses on understanding the structural basis underlying transitions between oligomeric states found in nature, as our mutational engineering of the 2-to-6 enzyme recapitulates the evolutionary trajectory taken by form II RuBisCOs when assembling hexamers from dimers.…”
Section: Engineering Increased Oligomeric Complexitymentioning
confidence: 99%
“…Several recent approaches hold promise and indicate that novel strategies implementing modified carbon-fixing machinery could lead to substantial improvements over the status quo. For example, a recent study inspired by the packed arrangement of RuBisCO within carboxysomes generated synthetic stacked assemblies of RuBisCO that exhibited enhanced catalytic activity and stability (Zeng et al, 2022). Incorporation of RuBisCO activase within carboxysomes is another strategy to reduce the inactivation of RuBisCO and enhance carbon-fixation (Chen et al, 2021).…”
Section: Synthetic Biology Applications and Inspirations Based On Ccmsmentioning
confidence: 99%